The Anti-Inflammatory Role of Annexin-1 in Arthritis - Yang, Yuan H.; Morand, Eric F. (Current Rheumatology Reviews, 2006)
Annxine-1 (Anx-1), a member of the annexin superfamily of calcium- and phospholipid- binding proteins, is induced by glucocorticoids (GC) and functions as a mediator of their anti-inflammatory effects. The wide range of effects of Anx-1 includes inhibition of leukocyte recruitment, suppression of the production of inflammatory mediators and cytokines, and induction of apoptosis in inflammatory cells. This profile of activity suggests that the inhibitory effects of Anx- 1 would be beneficial in the pathological context of rheumatoid arthritis (RA). Anx-1 is expressed in human RA synovial tissue and cells, and has recently been identified as an important endogenous anti-inflammatory mediator in multiple animal models of RA. Emerging data on the mechanisms of action of Anx-1 suggest it acts to inhibit mitogen activated protein (MAP) kinases, through as yet unidentified mechanisms, thereby inhibiting pro-inflammatory pathways known to be important in RA. Anx-1 treatment strategies, especially as an alternative to GC therapy, may be valuable in RA and other inflammatory diseases.
Keywords: Experimental Arthritis